2006
DOI: 10.1002/bjs.5496
|View full text |Cite
|
Sign up to set email alerts
|

Increased angiogenic response but deficient arteriolization and abnormal microvessel ultrastructure in critical leg ischaemia

Abstract: A physiological angiogenic response was found in CLI, but the microvessels had an abnormal ultrastructure. A lack of active cell proliferation suggests that the angiogenic response may have been exhausted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…A meta-analysis of 33 trials (38) reported the mean effect of exercise therapy on the ankle to brachial blood pressure index (ABI) to be trivial (0.03 Ϯ 0.06). Thus factors other than blood flow, e.g., the skeletal muscle structure, likely contribute the reduction in exercise tolerance in PAD patients and the improvement seen with exercise therapy.Pericapillary basement membrane thickening (7,8,24) and alterations of the volume density (V v ) of mitochondria (V v mito ) (1, 15) are examples of ultrastructural changes in skeletal muscle in patients with CLI, the late, most severe stages of PAD. However, skeletal muscle samples from CLI patients are heterogeneous and contain large deposits of fat and connective tissue, and there is a higher proportion of degenerated fibers compared with that observed in patients with IC (11), which limits their potential to be used in quantitative investigations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 33 trials (38) reported the mean effect of exercise therapy on the ankle to brachial blood pressure index (ABI) to be trivial (0.03 Ϯ 0.06). Thus factors other than blood flow, e.g., the skeletal muscle structure, likely contribute the reduction in exercise tolerance in PAD patients and the improvement seen with exercise therapy.Pericapillary basement membrane thickening (7,8,24) and alterations of the volume density (V v ) of mitochondria (V v mito ) (1, 15) are examples of ultrastructural changes in skeletal muscle in patients with CLI, the late, most severe stages of PAD. However, skeletal muscle samples from CLI patients are heterogeneous and contain large deposits of fat and connective tissue, and there is a higher proportion of degenerated fibers compared with that observed in patients with IC (11), which limits their potential to be used in quantitative investigations.…”
mentioning
confidence: 99%
“…Pericapillary basement membrane thickening (7,8,24) and alterations of the volume density (V v ) of mitochondria (V v mito ) (1, 15) are examples of ultrastructural changes in skeletal muscle in patients with CLI, the late, most severe stages of PAD. However, skeletal muscle samples from CLI patients are heterogeneous and contain large deposits of fat and connective tissue, and there is a higher proportion of degenerated fibers compared with that observed in patients with IC (11), which limits their potential to be used in quantitative investigations.…”
mentioning
confidence: 99%
“…Blood vessels in the MCL of ACL-t knees do not lack smooth muscle. [2]. Our focus has centered on the pathologic changes that occur in the MCL following rupture of the anterior cruciate ligament.…”
mentioning
confidence: 99%
“…Following anterior cruciate ligament (ACL) rupture, hypertrophy of the medial collateral ligament (MCL), capsule and synovium occur [2], preceding meniscal tears, cartilage lesions, and sub-chondral sclerosis ultimately leading to osteoarthritis [2]. Our focus has centered on the pathologic changes that occur in the MCL following rupture of the anterior cruciate ligament.…”
mentioning
confidence: 99%
“…This is followed by the degradation of the basement membrane, reorganization of original vessel walls and controlled proteolysis of the matrix molecules [20][21][22][23]. Angiopoietin-1 (Ang-1) is of particular interest because receptors for angiopoetin are located in endothelial cells [16,17].…”
Section: Discussionmentioning
confidence: 99%